2022
DOI: 10.1108/ijse-04-2020-0230
|View full text |Cite
|
Sign up to set email alerts
|

Poverty status of rural households in Nigeria: a gendered perspective

Abstract: PurposePoverty is endemic in rural Nigeria and gender disparity in access to productive resources is a major cause of poverty in the area. Poverty status of rural households along gender line was, therefore, investigated in this study.Design/methodology/approachPanel data from 2010/2011 (wave 1) and 2015/2016 (wave 3) of the Living Standard Measurement Survey (LSMS) for Nigeria were used for the study. Data were analysed using Foster, Greer and Thorbecke (FGT) poverty indices and binomial panel logistic model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Adepoju [ 11 ] found that multidimensional poverty among rural households in Nigeria was mainly chronic, with education and assets dimensions contributing most to the incidence and severity of poverty. Oyewunmi and Obayelu [ 12 ] investigated the poverty status of rural households in Nigeria from a gendered perspective, using panel data from the Living Standard Measurement Survey, and found that poverty status was influenced by gender. Furthermore, Adamu and Michael [ 13 ] emphasized the importance of investigating socio-economic factors and other variables that determine poverty among women farmers in rural areas in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Adepoju [ 11 ] found that multidimensional poverty among rural households in Nigeria was mainly chronic, with education and assets dimensions contributing most to the incidence and severity of poverty. Oyewunmi and Obayelu [ 12 ] investigated the poverty status of rural households in Nigeria from a gendered perspective, using panel data from the Living Standard Measurement Survey, and found that poverty status was influenced by gender. Furthermore, Adamu and Michael [ 13 ] emphasized the importance of investigating socio-economic factors and other variables that determine poverty among women farmers in rural areas in Nigeria.…”
Section: Introductionmentioning
confidence: 99%